2019
DOI: 10.1093/rpd/ncz096
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Absorbed Dose Rate in Air by Car-Borne Survey in Namie Town, Fukushima Prefecture After the Fukushima Daiichi Nuclear Power Plant Accident

Abstract: The latest car-borne survey was carried out by Hirosaki University in order to grasp the local distribution of the absorbed dose rate in air after the evacuation order was lifted on Namie Town in 2017. The car-borne survey of absorbed dose rate in air was carried out on most of the roads which were accessible by car in Namie Town using a 3-in × 3-in NaI(Tl) scintillation spectrometer. The range of the absorbed dose rate in air was calculated to be 0.041–11 μGy h−1. The distribution maps of the absorbed dose ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The absorbed dose rates in air of the natural radionuclides, artificial ra-dionuclides, and their totals are 15-68, 14-11,861, and 47-11,900 nGy h −1 , respectively. The total absorbed dose rate in air obtained in this study is almost in agreement with the 0.041-11 µGy h −1 measured by Shiroma et al [21]. The absorbed dose rates in air of natural radionuclides, artificial radionuclides, and their totals in the evacuation order cancellation zone are 19-51, 14-2010, and 47-2040 nGy h −1 , respectively.…”
Section: Absorbed Dose Rate In Air and Dose Rate Mapsupporting
confidence: 91%
See 1 more Smart Citation
“…The absorbed dose rates in air of the natural radionuclides, artificial ra-dionuclides, and their totals are 15-68, 14-11,861, and 47-11,900 nGy h −1 , respectively. The total absorbed dose rate in air obtained in this study is almost in agreement with the 0.041-11 µGy h −1 measured by Shiroma et al [21]. The absorbed dose rates in air of natural radionuclides, artificial radionuclides, and their totals in the evacuation order cancellation zone are 19-51, 14-2010, and 47-2040 nGy h −1 , respectively.…”
Section: Absorbed Dose Rate In Air and Dose Rate Mapsupporting
confidence: 91%
“…In addition, internal and external exposures from artificial radionuclides are being evaluated [14][15][16][17][18][19], and monitoring posts are installed in various locations to continuously measure the ambient dose equivalent rate [20]. In 2017, Shiroma et al conducted a car-borne su rvey in Namie Town, Fukushima Prefecture, and reported that the absorbed dose rate in air was 0.041-11 µGy h −1 [21]. More than nine years have passed since the FDNPP accident, and the relative contribution of natural radiation to ambient dose equivalent rates is increasing because the dose of artificial radiation is decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…The ambient dose rate and detection rate of radiocesium were significantly higher in the ISF than in the evacuation order lifted area and SRRB in Futaba town and Okuma town (p < 0.001). In general, the efficient and thorough decontamination processes can reduce ambient dose by removing radioactive materials from affected areas (environmental remediation) 19 24 . In our previous study in Tomioka town, Fukushima Prefecture, a significant difference in ambient dose rate since 2017 was observed between the decontaminated and non-decontaminated areas 19 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our previous study, decontamination was carried out effectively in Tomioka, reducing the ambient dose rates in the decontaminated area by 71.9% (from 1.0 µSv/h to 0.32 µSv/h within 1 year) 12 . Other studies have also reported the effectiveness of decontamination for reducing ambient dose rates to a low level 13,14,17 . Therefore, our ndings suggest that the environmental radioactivity in the SRRB and evacuation-order-lifted areas was continuously stable at extremely low levels as a result of decontamination.…”
Section: Discussionmentioning
confidence: 99%